Correlations between polarisation states of W particles in the reaction e(-)e(+)-> W-W+ at LEP2 energies 189-209 GeV - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (2009)
In a study of the reaction e - e +→W - W + with the DELPHI detector, the probabilities of the two W particles occurring in the joint polarisation states transverse-transverse (TT), longitudinal-transverse plus transverse-longitudinal (LT) and longitudinal-longitudinal (LL) have been determined using the final states WW→lvnq̄q (l=e,μ). The two-particle joint polarisation probabilities, i.e. the spin density matrix elements ρ TT, ρ LT, ρ LL, are measured as functions of the W - production angle, W-at an average reaction energy of 198.2 GeV. Averaged over all W-, the following joint probabilities are obtained: ̄ TT=(67±8)%,̄ LT=(30±8)%̄LL=(3±7)%.These results are in agreement with the Standard Model predictions of 63.0%, 28.9% and 8.1%, respectively. The related polarisation cross-sections σ TT, σ LT and σ LL are also presented. © 2009 Springer-Verlag / Società Italiana di Fisica.